Up in Smoke: Public Attitudes Toward the Implementation of Recreational Marijuana Legislation (RML) - Mancini, Christina (Crime & delinquency, 2025)
Several states have adopted recreational marijuana legislation (RML). While the public favors RML, open questions remain concerning the specific implementation of legalization. Specifically, how do Americans feel the revenue from such sales should be spent? Relatedly, what justice reforms should be considered? Not least, what proportion of the public remains uncertain about these facets of regulation and how does this uncertainty impact policy preferences for investment and reform? These are important questions to examine given the public’s influence in the emergence of RML. Drawing on a 2022 national poll (N = 1,003), this study examines public attitudes toward investment strategies (e.g., public schools) and justice system responses due to legalization (e.g., expungement). Results suggest that most of the public approves of these measures. However, divides in favoring specific initiatives are evident. Implications are discussed.